Chemical composition and bioactivities of Juçara fruit bio-residues, a promising source of valuable molecules - Garcia, Jéssica A.A. (2019)
﻿Euterpe edulis Martius, popularly known as Juçara, is a native tree of the Atlantic Rainforest found predominantly in the states of the southern and southeastern regions of Brazil. Juçara fruit is a globose berry that, when ripe, acquires a dark purple shade and sweet pleasant taste. The industrial production of Juçara fruit pulp generates solid residues (peel) which are usually discarded [1]. The aim of the present work was to perform an unprecedented in-depth study on the bioactive components profile of E. edulis fruit peel. The nutritional composition of this material was estimated and its hydroethanolic extract was characterized in terms of phenolic compounds, besides antioxidant and antibacterial potential. Finally, the hepatotoxicity of the extract was assessed. A total of nineteen phenolic compounds was identified in Juçara peel. Seventeen were non-anthocyanin molecules: two phenolic acids, namely caffeic acid and a ferulic acid derivative; four flavanonols, corresponding to three dihydroquercetin (taxifolin) and one dihydrokaempferol (aromadendrin) glycoside derivatives; six flavones, assigned as apigenin C-glycoside derivatives; and five flavonols, among which quercetin-3-O-rutinoside, kaempferol-3-O-rutinoside, and isorhamnetin-3-O-rutinoside. The major components of the peel extract were the anthocyanins cyanidin-3-O-rutinoside and cyanidin-3-O-glucoside (5.32 and 6.23 mg/g of extract, respectively), which together accounted for more than 87% of the extract’s total phenolic content, which corroborates literature data [2, 3]. Anthocyanins are amidst the main compounds related to the great free radical-scavenging capacity of Juçara fruit, whereas a significant positive correlation with its general antioxidant capacity was observed (Shultz et al., 2016). The herein studied fruit peel extract presented expressive values of antioxidant capacity, assessed by five distinct methods, namely (1) oxidative haemolysis inhibition assay (OxHLIA), (2) inhibition of the production of thiobarbituric acid reactive substances (TBARS); (3) reduction of the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH); (4) reduction of the 2,2-azino-bis (3-ethylbenzothiazoline-6-sulphonate) cation (ABTS), and (5) reduction power of the ferric ion (FRAP). Furthermore, the results obtained for antioxidant activity were more expressive than the ones verified by other authors for Juçara residues [1]. The evaluated E. edulis extract showed no toxicity against a non-tumour liver primary culture PLP2, at the highest concentration assessed (400 μg/mL). The inhibitory activity displayed by the extract against both Gram-positive (Enterococcus faecalis, Listeria monocytogenes, and Methicillin-resistant Staphylococcus aureus - MRSA) and Gram-negative (Escherichia coli, Klebsiella pneumonia, Morganella morganii, and Pseudomonas aeruginosa) bacteria indicates the presence of an extensive spectrum of phytochemical constituents with antibiotic potential. Indeed, the extract was more effective than the antibiotic ampicillin against M. morganii and P. aeruginosa. Therefore, Juçara fruit residues could be used to produce high added-value food ingredients, both colorants and preservatives, following the circular bioeconomy concept and stimulating the Juçara production chain.